Will Widespread Synthetic Opioid Consumption Induce Epigenetic Consequences in Future Generations? - Gilardi, Federica; Augsburger, Marc; Thomas, Aurelien (Frontiers in Pharmacology, 2018)
A growing number of evidence demonstrates that ancestral exposure to xenobiotics (pollutants, drugs of abuse, etc.) can perturb the physiology and behaviour of descendants. Both maternal and paternal transmission of phenotype across generations has been proved, demonstrating that parental drug history may have significant implications for subsequent generations. In the last years, the burden of novel synthetic opioid (NSO) consumption, due to increased medical prescription of pain medications and to easier accessibility of these substances on illegal market, is raising new questions first in term of public health, but also about the consequences of the parental use of these drugs on future generations. Besides being associated to the neonatal abstinence syndrome, in utero exposure to opioids has an impact on neuronal development with long-term repercussions that are potentially transmitted to subsequent generations. In addition, recent reports suggest that opioid use even before conception influences the reactivity to opioids of the progeny and the following generations, likely through epigenetic mechanisms. This review describes the current knowledge about the transgenerational effects of opioid consumption. We summarize the preclinical and clinical findings showing the implications for the subsequent generations of parental exposure to opioids earlier in life. Limitations of the existing data on NSOs and new perspectives of the research are also discussed, as well as clinical and forensic consequences.